2015
DOI: 10.1038/ncomms8821
|View full text |Cite
|
Sign up to set email alerts
|

DOT1L cooperates with the c-Myc-p300 complex to epigenetically derepress CDH1 transcription factors in breast cancer progression

Abstract: DOT1L has emerged as an anticancer target for MLL-associated leukaemias; however, its functional role in solid tumours is largely unknown. Here we identify that DOT1L cooperates with c-Myc and p300 acetyltransferase to epigenetically activate epithelial–mesenchymal transition (EMT) regulators in breast cancer progression. DOT1L recognizes SNAIL, ZEB1 and ZEB2 promoters via interacting with the c-Myc-p300 complex and facilitates lysine-79 methylation and acetylation towards histone H3, leading to the dissociati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(157 citation statements)
references
References 39 publications
6
150
1
Order By: Relevance
“…Even though multidimensional scaling analysis showed differences between both groups of PCs ( Figure 1B), there were only 38 genes significantly deregulated (3 upregulated and 35 downregulated) in AL PCs (excluding 22 immunoglobulin coding genes, which are physiologically upregulated in normal PCs and mainly reflect differences between clonal vs polyclonal PCs; supplemental Excel File 1). Interestingly, the CDH1 and RCAN tumor-suppressor genes and the GLIPR1 and FAS proapoptotic genes [14][15][16][17][18] were all significantly downregulated in AL; in contrast, IFITM1, which has been associated with more aggressive solid tumors, 19 was overexpressed in clonal PCs. It is worth noting that CD19 and CD81 mRNAs were significantly decreased in AL, confirming the correlation between the iPEP and the GEP of clonal vs normal PCs.…”
Section: Resultsmentioning
confidence: 98%
“…Even though multidimensional scaling analysis showed differences between both groups of PCs ( Figure 1B), there were only 38 genes significantly deregulated (3 upregulated and 35 downregulated) in AL PCs (excluding 22 immunoglobulin coding genes, which are physiologically upregulated in normal PCs and mainly reflect differences between clonal vs polyclonal PCs; supplemental Excel File 1). Interestingly, the CDH1 and RCAN tumor-suppressor genes and the GLIPR1 and FAS proapoptotic genes [14][15][16][17][18] were all significantly downregulated in AL; in contrast, IFITM1, which has been associated with more aggressive solid tumors, 19 was overexpressed in clonal PCs. It is worth noting that CD19 and CD81 mRNAs were significantly decreased in AL, confirming the correlation between the iPEP and the GEP of clonal vs normal PCs.…”
Section: Resultsmentioning
confidence: 98%
“…Consequently, DOT1L is a drug target for MLL-rearranged leukemia [11, 12]. Furthermore, a few recent publications have reported that DOT1L plays crucial roles not only in leukemia, but also in solid tumors, such as breast cancer, esophageal squamous cell carcinoma, colorectal cancer, prostate cancer, and gastric cancer [1319]. Moreover, DOT1L inhibitors have shown effective suppression of proliferation, migration, and invasion of breast cancer [20].…”
Section: Introductionmentioning
confidence: 99%
“…EMT is a process whereby cells acquire morphologic and molecular alterations facilitating tumor metastasis and progression [23,[24][25][26]. In previous studies, EMT signaling has been suggested to play a critical role in resistance to DDP [27,28].…”
Section: Zeb2 Directly Suppresses Mir-203 Expression By Binding To Itmentioning
confidence: 99%